A novel strategy for the efficient decomposition of toxic sodium cyanate by hematite. (October 2020) - Dong, Kaiwei; Xie, Feng; Chang, Yongfeng; Chen, Chunlin; Wang, Wei; Lu, Diankun; Gu, Xiaowei
Abstract: Toxic sodium cyanate is always present in cyanide-contaminated waste. A new technology for the efficient decomposition of toxic sodium cyanate by hematite was first proposed in this study. The decomposition of sodium cyanate under various atmospheres has been studied. Studies show that sodium cyanate decomposes above 782 °C in Ar and above 627 °C in air. Sodium cyanate does not decompose even roasted at 400 °C for 120 min in air. Hematite does not promote the decomposition of sodium cyanate in Ar. However, almost all sodium cyanate decomposes efficiently at 400 °C and the mass ration of hematite to sodium cyanate of 1:1 for 30 min in air or oxygen atmosphere. The increased mass ratio of hematite to sodium cyanate and roasting temperature can both favor the efficient decomposition of sodium cyanate. The efficient decomposition of sodium cyanate occurs within 30 min, and it is almost stagnant with the prolongation of roasting time. When roasted in air or oxygen in the presence of hematite, sodium cyanate decomposes to Na2 CO3, CO2 and N2 and a small amount of NaNO3 and NOx . The optimal efficient decomposition of sodium cyanate is to roast above 400 °C for 30 min in air or O2 at a mass ration of hematite to sodium cyanate greater than 1:1. Highlights: The initial decomposition of NaCNO is at 782 °C in air or 627 °C in Ar. The decomposition of NaCNO is completed at 400 °C in air or O2 with Fe2 O3 addition. NaCNO decomposes to Na2 CO3, NaNO3, CO2 and N2 in air or O2 with Fe2 O3 addition.